THE EXPERIENCE OF HYPOGAMMAGLOBULINEMIA TREATMENT IN CHILDREN - Popov, N. N.; Savvo, A. N.; Piontkovsky, O. V.; Timokhina, N. I.; Dyachenko, E. A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Children are often treated in non-core healthcare establishments and receive consultation of a pediatric immunologist too late when they already suffer from irreversible changes in various organs and body systems. For the main purpose to expand practical doctors’ knowledge about humoral immunity primary immunodeficiencies (PID) description of two cases of hypogammaglobulinemia in children (boys) aged 10 years is provided though clinical manifestation of the disease began in the early childhood. It was shown that proper diagnostics of PID allows providing adequate substitutive therapy and preventing children disability.